An Analysis of the Influential Factors of Violations in Urban-Rural Passenger Transport Drivers - Yun Xiao; Haoyun Liu; Zijun Liang (Journal of Advanced Transportation)
Road passenger transport is important for keeping urban and rural areas connected. In order to explore the traffic safety mechanisms behind urban and rural passenger transport, the personal attributes of urban-rural bus drivers from different areas were investigated. Based on the binary logistic regression model, an impact analysis model of 14 indicators of bus driver violations was established. The results showed that personality, gender, bus route, road conditions, and nap habits were important factors that affect driver violations. Female drivers violated slightly more (27.7%) than male drivers (26.2%), but male drivers violated multiple times (2.1), which was significantly higher than female drivers (1.5). Drivers with choleric personality were more likely to violate the traffic rules than others. Rural bus drivers violated significantly more (32.7%) than urban bus drivers (8%). The violation proportion of drivers who usually take naps but were deprived of naps (35.3%) was higher than that of drivers who have no nap habits (21.8%). The research results can act as a reference for improving urban-rural traffic safety.